Optimization of the total production time by splitting complex manual assembly processes - Kleiza, Vytautas; Tilindis, Justinas (Nonlinear Analysis: Modelling and Control, 2020)
In this article, the minimization of the learning content in the total processing time is studied. Research is based on manual automotive wiring harness assembly, with unstable demand, fluctuating order quantities and enormous product variety. Such instability in manual production environment results that assembly is always at the start-up or learning phase, thus, operational times are greater than standard and operational efficiency is significantly reduced. Since a lot of research is done on learning time calculation, there is still lacking studies that address learning time reduction in such production situation. The methodology proposed in this article addresses reduction of learning time by splitting and simplifying complex assemblies of automotive wiring harnesses. Experimental results from the company indicate that this approach enables to optimize learning time and increase operational efficiency.
Keywords: manual assembly; manufacturing optimization; operating time; wiring harness; learning curve